Pengembangan Media Pembelajaran Augmented Reality Mata Pelajaran IPA Sistem Tata Surya - Susilaningsih, Susilaningsih; Fichan, Achmad Maulana Iqbal; Praherdhiono, Henry; Prihatmoko, Yulias (Universitas Negeri Malang, 2023)
The learning process requires media to help teachers explain the material. The role of media in learning, especially in science subjects, is needed. However, at Mi Ar Raudah Lawang there is no learning media other than textbooks that can facilitate science learning, especially in the subject of the Solar system. In illustrated textbooks, students can less visualize real objects that cannot be seen directly. The purpose of developing the solar system is Augmented Reality media to be an alternative media in the process of learning science at Mi Ar Raudhah Lawang. Augmented Reality was developed to facilitate science subject matter, especially helping students with visual learning styles in learning. This development model uses the Lee & Owens model. This study received positive responses from media experts and material experts. The results of trials to students also get a positive score. Based on the results of the study showed that Augmented Reality developed can help teachers in teaching the solar system to students. And students can understand the solar system material well.Abstrak Proses pembelajaran membutuhkan media untuk membantu guru menjelaskan materi. Peran media dalam pembelajaran terutama dalam mata pelajaran IPA sangat dibutuhkan. Akan tetapi di MI Ar Raudah Lawang belum tersedia media pembelajaran selain buku teks yang dapat memfasilitasi pembelajaran IPA khususnya pada mata pelajaran Sistem Tata Surya. Pada buku teks bergambar, siswa kurang dapat memvisualisasikan objek nyata yang tidak dapat dilihat secara langsung. Tujuan pengembangan media Augmented Reality sistem tata surya menjadi alternatif media dalam proses pembelajaran IPA di MI Ar Raudhah Lawang. Augmented Reality dikembangkan untuk memfasilitasi materi pelajaran IPA khususnya membantu siswa dengan gaya belajar visual dalam pembelajaran. Model pengembangan ini menggunakan model Lee & Owens. Penelitian ini mendapatkan tanggapan yang positif dari ahli media dan ahli materi. Hasil uji coba kepada siswa juga mendapatkan skor yang positif. Berdasarkan hasil penelitian menunjukkan bahwa Augmented Reality yang dikembangkan dapat membantu guru dalam mengajarkan sistem tata surya kepada siswa. Serta siswa dapat memahami materi sistem tata surya dengan baik.